Stormorken Syndrome Caused by a p.R304W STIM1 Mutation: The First Italian Patient and a Review of the Literature - Borsani, Oscar; Piga, Daniela; Costa, Stefania; Govoni, Alessandra; Magri, Francesca; Artoni, Andrea; Cinnante, Claudia M.; Fagiolari, Gigliola; Ciscato, Patrizia; Moggio, Maurizio; Bresolin, Nereo; Comi, Giacomo P.; et al. (Frontiers in Neurology, 2018)
Stormorken syndrome is a rare autosomal dominant disorder characterized by a complex phenotype including tubular aggregate myopathy (TAM), bleeding diathesis, hyposplenism, mild hypocalcemia and additional features such as miosis and mild intellectual disability (dyslexia). Stormorken syndrome is caused by autosomal dominant mutations in the STIM1 gene, which encodes an endoplasmic reticulum Ca2+ sensor. Here, we present the clinical and molecular features of a 21-year-old Italian female with Stormorken syndrome. The STIM1 gene sequence identified a c.910C > T transition in a STIM1 allele (p.R304W). The p.R304W mutation is a common mutation that is responsible for Stormorken syndrome and is hypothesized to cause a gain of function effect associated with an increase in Ca2+. A review of published STIM1 mutations (n = 50) and reported Stormorken patients (n = 11) suggested a genotype-phenotype correlation with mutations in a coiled-coil cytoplasmic domain associated with complete Stormorken syndrome, while other pathological variants outside this region were more often linked to an incomplete phenotype. Our study describes the first Italian patient with Stormorken syndrome, contributes to the genotype/phenotype correlation and highlights the possibility of directly investigating the p.R304W mutation in the presence of a typical phenotype.